Annotated record of the detailed examination of Mn deposits from DSDP Site 61, Leg 7 (Core 61-1) - Edward L Winterer; William R Riedel; Ralph Moberly; Johanna M Resig; Loren W Kroenke; E L Gealy; G Ross Heath; P Bronnimann; E Martini; Thomas R Worsley (PANGAEA, 1971)
The results at Site 59 suggested that Mesozoic sediments are present beneath a thin Tertiary cover in the region north of the Caroline Ridge near the Mariana Trench. Since one of the principal objectives of the drilling program was to find old Pacific crust, and since the section at Site 59 was not fully penetrated, it seemed worth a determined effort to go beyond the level reached at Site 59, somewhere in the same general area, in an attempt to reach basement. As the reflection profile taken by Argo (SCAN Leg V) through Site 59 shows the section above thesmooth basement reflector (Horizon B?) thinning northwestward from about 0.3 to 0.15 second, by loss of part of the lower "transparent" layer, this is were Site 61 was located.
Supplement to: Winterer, EL et al. (1971): Site 61. In: Winterer, E.L.; et al., Initial Reports of the Deep Sea Drilling Project, 7, Initial Reports of the Deep Sea Drilling Project, 7, U.S. Government Printing Office, VII, 27-47, https://doi.org/10.2973/dsdp.proc.7.103.1971